UN NUEVO METODO PARA AJUSTE LINEAL BASADO EN EL EQUILIBRIO DE TORQUES - Sisniegas Charcape, G. E. (2006)
An alternative method is presented here to find the adjusted straight line equation for a population of points with every level of dispersion. This method gives two solutions: The adjusted straight line equation to such population of points and its corresponding perpendicular straight line equation. This new method contrasts with the classical method of linear regression in its accuracy and its independence of dispersion level of data. While by classical method, the solutions are always ambivalent, approached and dependent with dispersion level of data, the new method gives another solution to the adjusted straight line, which is identified as the adjusted perpendicular straight line equation (the transversal equation) to the same population of points.